Autoantibodies to Phospholipids and to the Coagulation Proteins in AIDS - Abuaf, N; Laperche, S; Rajoely, B; Carsique, R; Deschamps, A; Rouquette, A M; Barthet, C; Khaled, Z; Marbot, C; Saab, N; Rozen, J; Girard, P M; Rozenbaum, W (Thrombosis and Haemostasis, 1997)
In HIV-1 infection, an increased prevalence of anticardiolipin autoantibodies (aCL) and lupus anticoagulant (LA) has been described. In order to see if these antibodies are isolated or, like in autoimmune diseases, associated with hematological disorders and with antibodies to other phospholipids and to proteins of coagulation, we investigated 3 groups of patients: 1. 342 HIV-1 infected patients, 2. 145 control patients including 61 systemic lupus erythematosus (SLE) patients, 58 patients with a connective tissue disease, 15 patients with stroke, 11 patients with syphilis and 3.100 blood donors. In HIV-1 infection antiprothrombin (aPrT) antibodies were present in 25% of patients, the prevalence of antiphosphatidylcholine antibodies (aPC) (50%) was almost as high as aCL (64%), and 39% had both antibodies. Absorption on liposomes of the latter revealed an heterogeneous mixture of aCL and aPC or cross-reacting antibodies. In contrast with SLE, anti-β2-glycoprotein I (4%), LA (1%), biological false positive test for syphilis (0.3%), thrombosis (p <0.001) were uncommon. In HIV-1 infection, antiphospholipid antibodies do not associate with features linked to them in SLE or syphilis.